1990
DOI: 10.1254/jjp.54.375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kamikihi-To, a Traditional Chinese Medicine, on Passive and Conditioned Avoidance Performance Impairment in Senescence Accelerated Mouse (SAM)

Abstract: Abstract-Effectsof Kamikihi-To (KMK), a traditional Chinese medicine (Chinese name: Jia-Wei-Gui-Pi-Tang), on learning performance impairment caused by aging were evaluated in senescence accelerated mice (SAM). Normal diet con taining 8% KMK extract was given to SAM-P/8, a senile-prone strain, and to SAM R/1, a resistant strain, from 2 months old. Effects of KMK on learning performance were evaluated in 5 and 10 month old SAM using step through and step down type passive avoidance tests and shuttle box and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…In addition to exerting an anxiolytic effect, it has been reported that KKT improved the cognitive ability of alco holic patients (1). Furthermore, it has been shown that KKT improves learning performance in the senescent ac celerated mouse (2). These findings suggest that KKT may ameliorate anxiety, as well as memory impairment, in the elderly.…”
mentioning
confidence: 85%
“…In addition to exerting an anxiolytic effect, it has been reported that KKT improved the cognitive ability of alco holic patients (1). Furthermore, it has been shown that KKT improves learning performance in the senescent ac celerated mouse (2). These findings suggest that KKT may ameliorate anxiety, as well as memory impairment, in the elderly.…”
mentioning
confidence: 85%
“…In a pre vious study, we showed that KMK ameliorated both ethanol-induced and electroconvulsion-induced memory impairment in mice (1). KMK also antagonized memory deficits in the senescence-accelerated mouse (SAM), which is characterized by age-related deficits in learning performance (2). Egashira et al (3) have reported that KMK activated some cholinergic biochemical markers in the brains of aged rats.…”
mentioning
confidence: 90%
“…Some papers have reported favourable results in animals with cognitive impairments using extracts of a single herbal drug or traditional prescriptions (Petkov et al, 1993;Amagaya et al, 1990;Nishizawa et al, 1990;Nishiyama et al, 1994;Xie et al, 1996). It may be possible to find an effective treatment in the field of ancient traditional Chinese medicine system for combatting these kinds of cognitive diseases.…”
Section: Introductionmentioning
confidence: 99%